A quantitative study on physical and chemical effects of limestone powder on properties of cement pastes. (20th April 2019) - Wang, Dehui; Shi, Caijun; Farzadnia, Nima; Jia, Huangfei; Zeng, Rong; Wu, Youwu; Lao, Lilin
Highlights: The physical and chemical effects of limestone powder (LP) were calculated. The chemical effect of LP was influenced by its particle size and amount of LP at 3d. The particle size and amount of LP had little effect on its chemical effect at 180d. Abstract: The study aims to quantitatively calculate the physical and chemical effects of limestone powder (LP) with four average particle sizes and two amounts in cement pastes by using thermal gravimetric analysis (TGA), X-ray diffraction (XRD), mercury intrusion porosimetry (MIP) techniques. At 3d, as the average particle size of LP decreased from 32 to 6 μm, the consumed CaCO3 content in LP increased from 0.67% to 1.71%, and the chemically reactive portion of LP increased from 1.15% to 2.95%. However, at 180d, the consumed CaCO3 content and chemically reactive portion of LP was almost 2.4% and 4.2%, respectively. At 3d, as the LP content increased from 25% to 50%, the consumed CaCO3 content in LP increased from 1.71% to 2.02%, and the chemically reactive portion of LP increased from 2.95% to 3.5%. However, at 180d, the differences of consumed CaCO3 content and chemically reactive portion of LP between cement pastes with different LP content were limited. The physical and chemical effects of limestone powder on the compressive strength of cement pastes were calculated. At 180d, as the average particle size of LP decreased from 32 to 6 μm, the contribution of chemical effect of LP on the compressive strength of cement pastes increased from 1.01% to 1.08% while the contribution of physical effect decreased from 21.19% to 20.03%.